Giant pyroelectric properties in La and Ta co-doped lead-free 0.94Na0.5Bi0.5TiO3-0.06BaTiO3 ceramics - Balakt, Ahmed M.; Shaw, Christopher P.; Zhang, Qi (Elsevier, 2017)
La and Ta co-doped Lead-free 0.94NBT-0.06BT ceramics were synthesized by a conventional solid-state route. The compositions remain at a morphotropic phase boundary. The depolarization temperature (Td) decreased with increasing doping contents. The room temperature (RT) pyroelectric coefficient (p) was highly enhanced compared with undoped material (3.15 × 10−4 C m−2 °C−1) and reached 12.9 × 10−4 C m−2 °C−1, whereas, at Td, 58.6 × 10−4 C m−2 °C−1 could be obtained rather than 23.9 × 10−4 C m−2 °C−1 for undoped materials. The pyroelectric figure of merits, Fi and Fv, also showed a huge improvement from 1.12 × 10−10 m v−1 and 0.021 m2 C−1 of undoped material to 4.61 × 10−10 m v−1 and 0.078 m2 C−1 of doped materials at RT, and to 20.94 × 10−10 m v−1 and 0.28 × 10−10 m2.C−1 at Td. RT FC values are ∼2.40, 2.46, and 2.57 (×10−9 C cm−2 °C−1) at frequency 33, 100 and 1000 (Hz) respectively, at La = Ta = 0.2%. The pyroelectric coefficient achieved at RT in this study is almost one order of magnitude higher than PZT materials, furthermore, the figure of merits of the new compositions are comparable with or even better in those of PZT materials and other lead-free ceramics. The improvement in the pyroelectric properties makes La and Ta co-doped NBT-0.06BT ceramics possible materials to replace lead-containing PZT ceramics for infrared detector materials at a wide temperature range.
Keywords: Electroceramic; Lead-free ceramics; Lanthanum and tantalum co-doping NBT-0.06BT; Morphotropic phase boundary (MPB); Depolarization temperature; Pyroelectric properties; Figure of merits